جدليّةُ التعلّق بين صفةِ الكلام الإلهي ومراتبِ العلم الأزلي: دراسةٌ تحليليّة لِمفهومِ التوسّط الوجودي في نظريّات المتكلّمين: The Dialectic Between the Attribute of Divine Speech and the Degrees of Eternal Knowledge: An Analytical Study of the Concept of Ontological Mediation in Theories of the Mutakallimūn - Dr Mehfooz Ahmad Bhatti (AL-IDRAK JOURNAL, 2025)
This study examines the complex relationship between the attribute of Divine Speech (ṣifat al-kalām) and the gradations of eternal knowledge (ʿilm azalī) within classical Sunni kalām. It focuses on the analytical notion of ontological mediation (al-tawassuṭ al-wujūdī) as articulated by prominent mutakallimūn, exploring how divine speech functions not merely as a communicative act but as a metaphysical bridge between God’s eternal knowledge and the contingent cosmos. By examining Ashʿarī, Māturīdī, and later kalām commentaries, the research elucidates the dialectical tension inherent in reconciling divine immutability with the dynamic creation of the world. The paper demonstrates that the attribute of Divine Speech operates in a stratified ontology, wherein each degree of eternal knowledge corresponds to specific modes of manifestation in the created order. It interrogates how ontological mediation facilitates the translation of divine intent into accessible forms, enabling creatures to participate meaningfully in a divinely ordered reality without compromising God’s transcendence. Additionally, the study engages with debates over whether these theological constructions preserve epistemic transparency for human understanding or whether they deliberately retain an element of divine inscrutability. Through a comparative analytical methodology, the research highlights both convergences and divergences among classical scholars, shedding light on the nuanced interconnections between attributes, knowledge, and creation. The findings reveal that ontological mediation is not merely a technical device but a central epistemic and metaphysical principle that underpins classical Islamic theology’s approach to divine speech, eternal knowledge, and the intelligibility of the universe.